Efek Pemberian Ekstrak Etanol Akar Kolesom (Talinum triangulare Willd) terhadap Spermatogenesis Tikus Putih - Nugroho, Yun Astuti; Rahayu, Lestari; Susanti, Ratna Indah (Jurnal Kefarmasian Indonesia, 2012)
In Indonesia infertility is still a problem for married couples, because 10-15% of married couples suffer from infertility. Infertility can be caused by the husband and wife, but in reality 40-60% are caused by the husband. Data infertility based on analysis of cement, which is one important way to determine the level of male fertility. Cement circumstances that can cause infertility, among others, the less the number of spermatozoa, sperm motility is low, the velocity of spermatozoa and so on. Kolesom (Talinum triangulare Willd) can increase the number and motility of spermatozoa and to increase testosterone levels. The study aims to determine the effect of kolesom root extract on spermatogenesis of male Wistar rats. The effect of kolesom root extract on spermatogenesis using the WHO (2000) with animal white mouse. 225 doses of ethanol extract; 675 and 2025 mg / kg. administered orally for 45 days. Distilled water as a control and comparative dosage Korean Ginseng 225 mg / kg. The results of the study, kolesom extract doses 225; 675 and 2025 mg / kg BB given for 45 days did not lose reproductive organ testis and epididymis can still increase the number of A spermatogonia, pachytene stage primary spermatocytes and the diameter of seminiferous.